1994
DOI: 10.1111/j.1348-0421.1994.tb01852.x
|View full text |Cite
|
Sign up to set email alerts
|

Complement‐Mediated Killing of Borrelia garinii —Bactericidal Activity of Wild Deer Serum

Abstract: Abstract:The susceptibility of Borrelia garinii to fresh wild deer sera was determined by incubating strain SIKA2 at 10% serum concentration for 1 hr at 37 C in an in vitro bactericidal assay. Each serum showed bactericidal effects at various levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…The level of complement activity in serum has been found to be an important intrinsic factor determining the reservoir competence of lizards, birds, and mammals for several genospecies of B. burgdorferi s.l. (Isogai et al, 1994;Kurtenbach et al, 1998;Kuo et al, 2000;Nelson et al, 2000). Our complement-protein assays demonstrated that untreated (preimmune) serum from domestic turkeys was moderately bacteriolytic for B. burgdorferi s.s. because 45% of spirochetes introduced into it were dead within 1 hr.…”
Section: Turkeys As Hosts Of Ectoparasitesmentioning
confidence: 62%
“…The level of complement activity in serum has been found to be an important intrinsic factor determining the reservoir competence of lizards, birds, and mammals for several genospecies of B. burgdorferi s.l. (Isogai et al, 1994;Kurtenbach et al, 1998;Kuo et al, 2000;Nelson et al, 2000). Our complement-protein assays demonstrated that untreated (preimmune) serum from domestic turkeys was moderately bacteriolytic for B. burgdorferi s.s. because 45% of spirochetes introduced into it were dead within 1 hr.…”
Section: Turkeys As Hosts Of Ectoparasitesmentioning
confidence: 62%
“…Components of the complement system form an ancient aspect of innate immunity in vertebrates (267) and even some invertebrates (268,269). Therefore, many animals which act as viral hosts or reservoirs for zoonoses also have an active complement system for targeting pathogens i.e., bats (270), cows (271), deer (272), pigs (273), rabbits (274), and rats (274), which the virus may have to overcome to avoid possible antiviral activity. Further viral mechanisms of complement regulation may therefore exist which have not yet been identified and the plasticity of viral genomes could result in the emergence of novel protein regulatory functions.…”
Section: Resultsmentioning
confidence: 99%
“…Although colilargos accounted for 32 of these infested rodents, three long-haired grass mice ( Abrothrix longipilis ) and two olive grass mice ( A. olivaceus ) were also infested. More studies of the rodent populations in this biotope will be required to determine whether and which of these rodent species can serve as reservoir hosts for borrelia.The fact that no infected I. stilesi were collected from pudus suggests that these animals, like deer of the Northern Hemisphere, are not competent reservoir hosts for LB borreliae (Telford, III et al, 1988; Isogai et al, 1994; Brunner et al, 2008; Kjelland et al, 2011). The recent introduction of red deer (Cervus elaphus) to the Chilean biotope where this study was carried out (Jakcsic et al, 2002) could provide an opportunity for an additional host for Ixodes ticks.…”
Section: Discussionmentioning
confidence: 99%